2011
DOI: 10.1007/s12522-011-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of maternal vascular remodeling during human pregnancy

Abstract: Remodeling of maternal spiral arteries by invasion of extravillous trophoblast (EVT) is crucial for an adequate blood supply to the fetus. EVT cells that migrate through the decidual tissue destroy the arterial muscular lining from the outside (interstitial invasion), and those that migrate along the arterial lumen displace the endothelium from the inside (endovascular invasion). Numerous factors including cytokines/growth factors, chemokines, cell adhesion molecules, extracellular matrix-degrading enzymes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 99 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…The process may initiate as early as before GA 8 weeks, while the establishment of uteroplacental circulation is completed at approximately GA 12 weeks. Hence, it is believed that stage 1 takes place before GA 12 to 20 weeks [ 38 ].…”
Section: Pathophysiology Of Preeclampsiamentioning
confidence: 99%
“…The process may initiate as early as before GA 8 weeks, while the establishment of uteroplacental circulation is completed at approximately GA 12 weeks. Hence, it is believed that stage 1 takes place before GA 12 to 20 weeks [ 38 ].…”
Section: Pathophysiology Of Preeclampsiamentioning
confidence: 99%
“…Meanwhile, EVTs reach the spiral arteries from the interstitial side (sometimes also called perivascular trophoblasts or—if present in the vessel wall—intramural trophoblasts) and embed themselves in fibrinoid material within the arterial walls. Endoarterial trophoblasts may partly replace the endothelium and further disrupt the arterial wall and finally open the spiral arteries as large and stiff tubes toward the intervillous space with all its physiological consequences in terms of blood flow toward the placenta [ 26 , 162 , 167 ]. It is plausible that some of the endoarterial trophoblasts crawl on top of the endothelium and may invade into the wall at a distant site again.…”
Section: Extravillous Trophoblast Subpopulations and Trophoblast Inva...mentioning
confidence: 99%
“…Interestingly, Fujiwara et al (2005b) found that the EVTs also expressed dipeptidyl peptidase IV to metabolize CCL5, therefore inhibiting the excessive cell invasion. This regulation of trophoblast invasion and differentiation function by the chemokine-CCR1 system is considered a key molecular mechanism of maternal vascular remodeling during human early pregnancy (Sato et al, 2012).…”
Section: Ccl3/ccl5/ccr1mentioning
confidence: 99%